Evaluating the Potential of Recycled Asphalt for Sustainable Road Construction: An Environmental and Economic Analysis - Muhamet Ahmeti; Milaim Ahmetaj; Visar Krelani (Salehan Institute of Higher Education, 2023)
Objective: This study investigated the possibility of using recycled asphalt for road construction and maintenance in Kosovo. Methods: By analyzing statistical data from the Ministry of Infrastructure based on the status of infrastructure, the life cycle of asphalt, and investments in this area, this study determined the amount of asphalt that needs to be recycled. Results: The results showed that 1454008.5 m3 of asphalt needs to be recycled in Kosovo. We studied using 10%, 15%, and 20% recycled asphalt in asphalt base courses. We determined the benefits of recycled asphalt in terms of environmental protection, energy savings, and low cost. Depending on the percentage of recycled asphalt, the savings in mineral mix ranged from 11% to 23% and the road bitumen dosage from 6 to 8.5%. Novelty/Improvement: The proposed method of reusing recycled materials can reduce the consumption of natural resources, energy, and financial costs and help protect the environment. Doi: 10.28991/CEJ-2023-09-06-014 Full Text: PDF